2015
DOI: 10.1080/15384101.2015.1078033
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of polo like kinase 1 in sarcomas induces apoptosis that is dependent on Mcl-1 suppression

Abstract: Sarcomas are rare cancers and the current treatments in inoperable or metastatic disease have not been shown to prolong survival. In order to develop novel targeted therapies, we tested the efficacy of polo-like kinase 1 (PLK-1) inhibitor (TAK-960) in sarcoma. All the sarcoma cell lines were sensitive to TAK-960 with IC50s in the low nanomolar range. We chose MPNST, CHP100 and LS141 for our studies and of which MPNST cells exclusively underwent polyploidy after a delay in mitosis for about 18 hours; CHP100 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The same study found that aberrant spindle accumulation was apparent with higher doses of Tak960. Another study demonstrated that Tak960 causes an induction of apoptosis, possibly due to a down regulation of Mcl-1 in sarcoma cells (75). Another Plk1 inhibitor, NMS-P937, has shown notable success in the reduction of osteosarcoma tumor growth (76).…”
Section: Plk1 As a Drug Targetmentioning
confidence: 99%
“…The same study found that aberrant spindle accumulation was apparent with higher doses of Tak960. Another study demonstrated that Tak960 causes an induction of apoptosis, possibly due to a down regulation of Mcl-1 in sarcoma cells (75). Another Plk1 inhibitor, NMS-P937, has shown notable success in the reduction of osteosarcoma tumor growth (76).…”
Section: Plk1 As a Drug Targetmentioning
confidence: 99%
“…3 ). Recent studies have shown Plk1 and Phospho-Plk1 accumulation upon exposure to Plk1 inhibition by TAK-960 and CBB2001, respectively [ 33 , 34 ]. At early time points, Plk1 levels remained constant in both sensitive and resistant cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown TAK-960 is an effective anti-proliferative agent in in vitro models of ovarian, colorectal, sarcoma, breast, and non-small cell lung cancers, among others [ 18 , 33 , 44 ]. We report TAK-960 exposure has a pronounced anti-proliferative effect on CRC cell lines and IC 50 is independent of common CRC driver mutations, including KRAS and p53 as previously reported [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we analyzed C1qbp expression because a previous study showed that C1qbp promotes cellular proliferation and resistance to cell death in breast cancer cell lines 25 . Second, we analyzed Mcl-1 expression because a previous study reported that Mcl-1 suppression was related to apoptosis caused by PLK1 inhibition in sarcomas 26 . In the sequencing data, C1qbp mRNA expression decreased depending on PLK1 knockdown (Fig.…”
Section: Resultsmentioning
confidence: 99%